Mapping research trends on development of scientific literacy assessment: A bibliometric analysis - Yasmine Hadiastriani; Prasetyorini Djarot (University of Muhammadiyah Malang, 2024)
This study conducts a bibliometric analysis to map the research trends and intellectual landscape surrounding the development of scientific literacy assessments in educational contexts from 2019 to 2023. Scientific literacy, which encompasses the ability to comprehend, evaluate, and apply scientific knowledge, has emerged as a crucial competency in science education. However, existing assessment tools often prioritize factual recall over deeper conceptual understanding and critical thinking abilities. To address this gap, there is a need for innovative assessment approaches that holistically evaluate students' scientific literacy across multiple dimensions. Through a systematic analysis of 185 relevant publications from the Scopus database, this study investigates the numerical distribution of literature by year, document type, journal, author, institution, and country. Additionally, it explores the prominent themes, evolving topic trends, and emerging clusters within the scientific literacy assessment research domain. Bibliometric techniques, including citation analysis, co-authorship networks, and keyword co-occurrence mapping, are employed to provide a comprehensive perspective. The findings reveal a steady increase in publications focused on scientific literacy assessments, reflecting the growing recognition of this research area. The analysis identifies highly influential journals, articles, authors, and institutions actively shaping the field. Furthermore, it highlights key research themes, such as secondary education, teacher professional development, and information literacy. However, the integration of scientific literacy assessments with artificial intelligence remains an underexplored area, presenting opportunities for future research.